Król Ryszard II - Shakespeare, William, 1564-1616 (Wydawnictwo Ktoczyta.pl, 2017)
Tells the story of the last two years of the life of King Richard II of England, from 1398-1400. After the king's decisions and actions come under criticism from some of his nobles, he is overthrown by Bolingboke (King Henry IV), imprisoned, and finally murdered.